2006
DOI: 10.2178/jsl/1154698590
|View full text |Cite
|
Sign up to set email alerts
|

Lowness and nullsets

Abstract: We prove that there exists a noncomputable c.e. real which is low for weak 2-randomness, a definition of randomness due to Kurtz, and that all reals which are low for weak 2-randomness are low for Martin-Löf randomness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 5 publications
1
52
0
Order By: Relevance
“…At this point, the reader might be tempted to conjecture that the corresponding lowness notions for difference randomness might coincide with K-triviality as they do in the case of lowness for weak 2-randomness [4,8]. We show a connection between the corresponding lowness notions for difference randomness and two other well-known lowness classes arising in the study of K-triviality.…”
Section: Relationships With Lowness Classesmentioning
confidence: 77%
See 1 more Smart Citation
“…At this point, the reader might be tempted to conjecture that the corresponding lowness notions for difference randomness might coincide with K-triviality as they do in the case of lowness for weak 2-randomness [4,8]. We show a connection between the corresponding lowness notions for difference randomness and two other well-known lowness classes arising in the study of K-triviality.…”
Section: Relationships With Lowness Classesmentioning
confidence: 77%
“…We recall that if R and S are classes of random reals, then Low(R,S) is the class of reals A such that R is a subset of S A . Then our A is in Low(W2R,ML) and thus it is K-trivial [4]. In particular, A must be low.…”
Section: Theorem 41 Suppose That a Is An Re Set Then A Is A Basementioning
confidence: 93%
“…of 'strong random sequences' still has measure 1 but none of its members have the defect 1. These developments are summarized in Downey et al (2006b). The goal of the present note is to offer a converging criterion for the strong random sequences.…”
Section: For Any Input I P Enters a Nonterminating Routine That Writmentioning
confidence: 98%
“…For example, it can be shown that X is weakly 2-random (i.e. in every Σ 0 2 class of measure 1) iff X is 1-random and its degree forms a minimal pair with ∅ (Downey, Nies, Weber, and Yu [48] plus Hirschfeldt and Miller (in [48]) for the hard direction). Hence no (weakly) 2-random real can bound a P A degree.…”
Section: Computability and Randomnessmentioning
confidence: 99%